2021
DOI: 10.3390/molecules26175126
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Association between γ-Cyclodextrin and Preyssler-Type Polyoxotungstate

Abstract: The development of hybrid materials based on polyoxometalates constitutes a strategy for the design of multifunctional materials. The slow evaporation of an aqueous solution of [NaP5W30O110]14− in the presence of γ-Cyclodextrin (γ-CD) led to the crystallization of a K6Na8{[NaP5W30O110]•(C48H80O40)}•23H2O (NaP5W30•1CD) supramolecular compound, which was characterized by single-crystal X-ray diffraction, IR-spectroscopy, thermogravimetric and elemental analyses. Structural analysis revealed the formation of 1:1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Compared with the previously reported porous POM-CD supramolecular frameworks using POMs as MBBs, 22–32 1 represents the first example featuring interconnected channels along two dimensions constructed from ({MnV 12 Ce 6 }{PW 10 V 2 } 2 ) ∞ IBBs. First, the infinite nature of such IBBs makes it hard for them to approach the primary/secondary faces of α-CD due to the size mismatch; secondly, the embedded {PW 10 V 2 } bears a negative charge of −5, which makes it to preferentially interact with the external surface of α-CD according to the reported Hofmeister series of Keggin-type POMs where [BW 12 ] 5− is located outside γ-CD due to the weak Hofmeister efffect.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Compared with the previously reported porous POM-CD supramolecular frameworks using POMs as MBBs, 22–32 1 represents the first example featuring interconnected channels along two dimensions constructed from ({MnV 12 Ce 6 }{PW 10 V 2 } 2 ) ∞ IBBs. First, the infinite nature of such IBBs makes it hard for them to approach the primary/secondary faces of α-CD due to the size mismatch; secondly, the embedded {PW 10 V 2 } bears a negative charge of −5, which makes it to preferentially interact with the external surface of α-CD according to the reported Hofmeister series of Keggin-type POMs where [BW 12 ] 5− is located outside γ-CD due to the weak Hofmeister efffect.…”
Section: Resultsmentioning
confidence: 94%
“…[22][23][24][25] Since the pioneering work of developing archetypal Keggin and Dawson-CD assemblies, 26,27 the scope of POM clusters has evolved from smaller Strandberg, Lindqvist and Anderson to bigger Preyssler, and even to gigantic Mo blue. 25,[28][29][30][31] In spite of these prominent advancements, the deliberate fabrication of porous ordered POM-CD systems is still challenging because of the dominant interacting modes between the POM clusters and native CDs mainly involving host-guest inclusion occurring at the primary or secondary face of CDs, which leads to easy blocking of the cavity of CDs and thus resulting in the formation of non-porous networks.…”
Section: Introductionmentioning
confidence: 99%
“…It is a well‐established method in host‐guest chemistry to highlight differences in diffusion rates when guest species are bound to a host molecule compared to that of when it is moving freely. [ 52 , 53 , 54 , 55 , 56 ] Figure 5 shows that BV 2+ guest and {Pd 84 } Ac host tumble at an average rate of 401 pm 2 s −1 and 207 pm 2 s −1 , respectively when they are alone in solution. In a 1 : 7 solution of the two components there is a significant decrease in the average diffusion coefficients for BV 2+ to 144 pm 2 s −1 and {Pd 84 } Ac to 113 pm 2 s −1 .…”
Section: Resultsmentioning
confidence: 99%
“…91 Most recently, Leclerc et al reported the formation of a 1 : 1 exclusion complex between γ-CD and a Preyssler-type anion, [NaP 5 W 30 O 110 ] 14− . 92 The large and highly charged anion interacts with the primary face of the γ-CD as revealed by single-crystal X-ray diffraction and 1 H NMR experiments.…”
Section: Introductionmentioning
confidence: 99%